The actions of methotrexate on endothelial cells are dependent on the shear stress-induced regulation of one carbon metabolism - Lang, Marie B.; Leung, Kit-Yi; Greene, Nicholas D.E.; Malone, Kerri M.; Saginc, Gaye; Randi, Anna M.; Kiprianos, Allan; Maughan, Robert T.; Pericleous, Charis; Mason, Justin C. (Frontiers in Immunology, 2023)
Objectives: The disease-modifying anti-rheumatic drug methotrexate (MTX) is recognized to reduce cardiovascular risk in patients with systemic inflammatory diseases. However, the molecular basis for these cardioprotective effects remains incompletely understood. This study evaluated the actions of low-dose MTX on the vascular endothelium. Methods: Human endothelial cells (EC) were studied under in vitro conditions relevant to inflammatory arthritis. These included culture in a pro-inflammatory microenvironment and exposure to fluid shear stress (FSS) using a parallel plate model. Respectively treated cells were analyzed by RNA sequencing and quantitative real-time PCR for gene expression, by immunoblotting for protein expression, by phosphokinase activity arrays, by flow cytometry for cell cycle analyses and by mass spectrometry to assess folate metabolite levels. Results: In static conditions, MTX was efficiently taken up by EC and caused cell cycle arrest concurrent with modulation of cell signaling pathways. These responses were reversed by folinic acid (FA), suggesting that OCM is a predominant target of MTX. Under FSS, MTX did not affect cell proliferation or pro-inflammatory gene expression. Exposure to FSS downregulated endothelial one carbon metabolism (OCM) as evidenced by decreased expression of key OCM genes and metabolites. Conclusion: We found that FSS significantly downregulated OCM and thereby rendered EC less susceptible to the effects of MTX treatment. The impact of shear stress on OCM suggested that MTX does not directly modulate endothelial function. The cardioprotective actions of MTX likely reflect direct actions on inflammatory cells and indirect benefit on the vascular endothelium.